Cyclobutane dication, (CH2)42+: a model for a two-electron four-center (2e-4c) Woodward–Hoffmann frozen transition state - Prakash, G. K. Surya; Rasul, Golam (Beilstein Journal of Organic Chemistry, 2019)
The structures of the elusive cyclobutane dication, (CH2)42+, were investigated at the MP2/cc-pVTZ and CCSD(T)/cc-pVTZ levels. Calculations show that the two-electron four-center (2e-4c) bonded structure 1 involving four carbon atoms is a minimum. The structure contains formally two tetracoordinate and two pentacoordinate carbons. The non-classical σ-delocalized structure can be considered as a prototype for a 2e-4c Woodward–Hoffmann frozen transition state. The planar rectangular shaped structure 2 with a 2e-4c bond was found not to be a minimum.
Keywords: cyclobutane dication; 2e-4c bond; frozen transition state; Woodward–Hoffmann rule

(untitled) - Oka, T. (Phys. Rev. Lett., 1980)

(untitled) - Kekulé, A. (Ann. Chem. Pharm., 1858)

(untitled) - Kekulé, A. (Z. Chem. (Leipzig, Ger.), 1867)

(untitled) - Olah, G. A.; Klopman, G.; Schlosberg, R. H. (J. Am. Chem. Soc., 1969)

Chemical Reactivity and Reaction Paths - Olah, G. A. (Wiley, 1974)

Hypercarbon Chemistry - Olah, G. A.; Prakash, G. K. S.; Wade, K.; Molnár, Á.; Williams, R. E. (John Wiley & Sons, Inc., 2011)

(untitled) - Bremer, M.; von Ragué Schleyer, P.; Schötz, K.; Kausch, M.; Schindler, M. (Angew. Chem., Int. Ed. Engl., 1987)

(untitled) - Prakash, G. K. S.; Krishnamurthy, V. V.; Herges, R.; Bau, R.; Yuan, H.; Olah, G. A.; Fessner, W. D.; Prinzbach, H. (J. Am. Chem. Soc., 1986)

(untitled) - Glukhovtsev, M. N.; von Ragué Schleyer, P.; van Eikema Hommes, N. J. R.; De M. Carneiro, J. W.; Koch, W. (J. Comput. Chem., 1993)

(untitled) - Prakash, G. K. S.; Krishnamurthy, V. V.; Herges, R.; Bau, R.; Yuan, H.; Olah, G. A.; Fessner, W. D.; Prinzbach, H. (J. Am. Chem. Soc., 1988)

(untitled) - Herges, R.; von Ragué Schleyer, P.; Schindler, M.; Fessner, W. D. (J. Am. Chem. Soc., 1991)

(untitled) - Goldstein, M. J.; Hoffmann, R. (J. Am. Chem. Soc., 1971)
and references cited therein.

(untitled) - Hoffmann, R.; Stohrer, W.-D. (J. Am. Chem. Soc., 1971)

Gaussian 09, Revision A.02 (Gaussian, Inc., 2009)

(untitled) - Alecu, I. M.; Zheng, J.; Zhao, Y.; Truhlar, D. G. (J. Chem. Theory Comput., 2010)

(untitled) - London, F. (J. Phys. Radium, 1937)

(untitled) - Ditchfield, R. (Mol. Phys., 1974)

(untitled) - Wolinski, K.; Hinton, J. F.; Pulay, P. (J. Am. Chem. Soc., 1990)

(untitled) - Schäfer, A.; Horn, H.; Ahlrichs, R. (J. Chem. Phys., 1992)

(untitled) - Gauss, J. (Chem. Phys. Lett., 1992)

(untitled) - Gauss, J. (J. Chem. Phys., 1993)

(untitled) - Harding, M. E.; Metzroth, T.; Gauss, J.; Auer, A. A. (J. Chem. Theory Comput., 2008)